Mining in Africa : Are Local Communities Better Off? - Chuhan-Pole, Punam; Dabalen, Andrew L.; Land, Bryan Christopher (Washington, DC: World Bank and Agence Francaise de developpement, 2017)
This study focuses on the local and regional impact of large-scale gold mining in Africa in the context of a mineral boom in the region since 2000. It contributes to filling a gap in the literature on the welfare effects of mineral resources, which, until now, has concentrated more on the national or macroeconomic impacts. Economists have long been intrigued by the paradox that a rich endowment of natural resources may retard economic performance, particularly in the case of mineral-exporting developing countries. Studies of this phenomenon, known as the “resource curse,” examine the economy-wide consequences of mineral exports.